STUDI DAN PEMANTAUAN KUALITAS AIR DI DAERAH ALIRAN SUNGA! (DAS) BADUNG - I Made Sara Wijana; I.G.A. Kunti Sri Pancadewi; Abd Rahman As-syakur (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Badung River is one of the river that across Denpasar city. As one of the rivers that passes through the city with a very dense population, along the river there are activities that has potentially degrade water quality. The aims of this study are to determine the water quality trend and status of water quality standards of Badung River from 2006 to 2009. The result analysis showed the water quality on Badung River declined in the upstream section and relatively stabl e in the middle and downstream section. This situation is result of the waste sources is relatively constant throughout the study period. The existence of DO, BODS, Nitrites, Phosphates, Coliform, and E. Coli is the water quality parameter that always exceeds the threshold of quality standard.